Meningkatkan Kemandirian Anak Usia 5-6 Tahun Melalui Strategi Discovery Learning - Suprihatin, Eny; Antonius Jhonwilson Neno; Ayu Simanullang (JURNAL TALITAKUM: JURNAL PENDIDIKAN KRISTEN ANAK USIA DINI, 2023)
Independence is the ability to do something by initiating, trying, courageous, without the help of others. This study discusses how to increase children's independence through Discovery Laerning's learning motede. This type of research uses literature studies by collecting data through various book materials, articles, and research results related to research studies which are then analyzed. After carrying out the screanning process, articles and books are selected as the final review. Data analysis techniques using content analysis methods aim to describe and infer the content of data sources. The purpose of this study is to obtain problem-solving learning strategies, based on the stages of the discovery learning learning model, things that affect independence in children, andteachers build children's independence through discovery learning learning strategies, Increasing independence in children through discovery learning strategies. Research results Through the Discovery Learning method in schools applied, teachers strongly support children to find out for themselves, solve problems on their own and even children can recognize themselves. Keywords: Child Independence, Discovery Learning, Teachers.